Polycentropus aileenae n. sp. (Trichoptera: Polycentropodidae), a caddisfly species from the eastern Nearctic, with new state records for members of the Polycentropus confusus Species Group - Orfinger, Alexander B.; Moulton, John K. (Zootaxa, 2021)
A new eastern Nearctic species of tube-making caddisfly of the genus Polycentropus Curtis 1835 (Trichoptera: Polycentropodidae) is described and illustrated based on adult males and females. Polycentropus aileenae n. sp., a member of the Polycentropus confusus Species Group, is reported from the Canadian province Nova Scotia and the U.S. states Tennessee and Pennsylvania. The species is diagnosed based on multiple aspects of the male genitalia, including inflection of the dorsal processes of the preanal appendages and the slightly recurved dorsum of the apex of the phallus. New U.S. state records of P. confusus Hagen 1861 and P. elarus Ross 1944 from Florida, and P. thaxtoni Hamilton & Holzenthal 1986 from Alabama, are also provided.